Regional pathways to complexity : settlement and land-use dynamics in early Italy from the Bronze Age to the Republican period - Attema, P. A. J.; Burgers, G.-J. L. M.; Leusen, Martijn van (Amsterdam archaeological studies, 2010)
Synthesizing almost thirty years of Dutch archaeological research in central and southern Italy, this book discusses and compares settlement and land use patterns from the late protohistoric period to the late Roman Republic. Considering both social and environmental factors, the authors analyze the long-term progression of indigenous Bronze Age tribal pastoralist societies towards the complexity of urbanized Roman society. Drawing on a decade of collaboration between Dutch and Italian researchers, this exhaustive study will be of great interest to students and scholars of Mediterranean archaeology.
Keywords: Land settlement : Italy : History; Excavations (Archaeology) : Italy; Italy : Antiquities; Italy : Historical geography; Italy : History